If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8 + t = -12 Solving -8 + t = -12 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + t = -12 + 8 Combine like terms: -8 + 8 = 0 0 + t = -12 + 8 t = -12 + 8 Combine like terms: -12 + 8 = -4 t = -4 Simplifying t = -4
| a^2-2ag+g^2=0 | | c^2-12=c | | (-8z-3z+5)+(-3z+9z+2)= | | m=-1-(-3) | | 13-2(3x+8)=7x-(x+11) | | 3(2x)(2x)= | | 14+3x=35 | | -4(5-3x)=76 | | y^2-16y+55= | | 5(-2/3)=-10/3 | | 39=12+3x | | 25c^2+70c+49=0 | | (5+a)(5a+3)=0 | | -2(2x+4)=-24 | | -5(x-y)=114 | | 2x=15-2 | | -9(-4)=36 | | -5x+y=114 | | 8+7x=6x+5 | | 17+7x=15+8x | | -5(x+y)=114 | | x^2-20x-3= | | -5x-y=114 | | (5+z)(5z+3)=0 | | 5u^2-39u-8=0 | | 934+1x=3x | | 2x+3/3-7x/6=2x/9+2 | | 2x^2+x+3= | | 40x+7.50=1250 | | 2x+3/3=2y-4 | | -1-4x=6x+9 | | 20-1/5d=3/10d+16 |